The Impact Of IFRS 16 Implementation On Tax Aggressiveness: Do Right-Of-Use Assets And Lease Liabilities Matter? - Sa’diyyah, Dewi Khalimatus; Herwanda, Reyhan; Firmansyah, Amrie (WIM Solusi Prima, 2024)
Implementing PSAK 73 in Indonesia requires companies to disclose right-of-use assets and lease liabilities in their financial statements. This study examines the impact of changes in the disclosure of right-of-use assets and lease liabilities due to the implementation of PSAK 73 on tax aggressiveness. The research sample consisted of financial statements of companies in the consumer non-cyclical sector listed on the Indonesian Stock Exchange (IDX) from 2020 to 2022. Using purposive sampling, the study used 24 companies with 72 observations. The impact of the change was tested using panel data linear regression. The results showed that right-of-use assets have a positive impact on tax aggressiveness, while lease liabilities do not have a significant impact on tax aggressiveness. This study contributes to the literature on PSAK 73 and its relationship with tax aggressiveness. The Directorate General of Taxes can use the findings to develop tax monitoring and auditing strategies.